Prevalência de sobrepeso, obesidade e atividade física em escolares de São Luís-MA e fatores associados - SILVA, Josenilde Sousa e (2006)
Transversal study in probabilistical sample from 1130 schoolchildren from 6 to 16 years, aiming to estimate the prevalence of obesity and overweight in that sample, as well as evaluating their level of physical activity. It was used as criterion diagnosis Index of Corporal Mass (IMC), according to Cole et el., and the triceps and subscapular skinfold thickness measurement. To evaluate the level of physical activity, an inquiry of physical activity of 24 hours adapted of Self Administered Physical Activity Checklist (SAPAC) was used. For the economical classification criterion was used based on the degree instruction of the responsible and estate of family consumption. Obesity prevalence was observed in 1,3% of the schoolchildren, much larger in male (2,2%) than female (0,6%); in the private school (2,7%) that in the public school (0,9%) and among the ones which lived together with smaller number of residents (4,5%) (p < 0,05). The overweight was more prevalent in the private school and in the economical class “A and B.” The overweight through IMC was also larger among the students of the 4th to 8th series (8,1%) and for the overweight given by the sum of the triceps and subscapular skinfolds thickness, only the color of the skin stayed as risk factor after the multivariable analysis. Most of the schoolchildren was classified as “very vigorous” (42,4%); and 46,7% of these spent less than two hours with sedentary activities. The public school presented larger percentile of “moderate” and “very vigorous” schoolchildren (35,2% and 44,4%, respectively) and the private school, larger percentile of “inactive/minimally active” ones (35,4%), (p<0,05). These findings indicate that the overweight and obesity seems they are not still constituted in a problem of great extension among the schoolchildren of São Luís public schools, however the obesity can be considered preoccupying in the private establishments of teaching.